TEACHING PREPOSITIONS (American Journal of Interdisciplinary Research and Development, 2023)
What are prepositions? They are those little words that help the connection of thoughts, ideas, and descriptions. They help the listener or the reader to know the direction, movement, condition, purpose, cause, manner, quantity, quality, identity, place, and time in the unfolding of any information or a story. Prepositions form a small but important word class, being very frequently used. In fact, the prepositions to, of, in, for, on, with, at, by, from are all in the top 25 words in English. Helping students understand and correctly use prepositions contributes greatly to their fluency. A clear understanding as to what prepositions are actually for is essential for the teacher, although it may not be necessary to go in detail into the grammar points below at all levels. [1, 13]